Mitra Sejati Medan Hospital Reputation Restoration Strategy in the Case of Swapped Baby - Stefanny Lasmanogi Simanjuntak; Anang Sujoko; Antoni (Global Writing Academica Researching & Publishing, 2022)
A good reputation is one of the main factors for successful performance, but its implementation is still being questioned in various agencies or organizations in Indonesia. This qualitative study aims to analyze and evaluate the success of the reputation restoration strategy for Mitra Sejati Hospital in Medan after the baby are swapped. This research involved two key informants (public relations and supervisors) who handled the case. The collected data were analyzed using the Miles and Huberman analysis techniques. The results of this study informed that Mitra Sejati Medan Hospital was quite slow in providing an initial response, so that the case was spread through the media. Furthermore, the hospital then used three stages, namely mortification, compensation, and collective action. Following up on the findings in this study, the reputation management of Mitra Sejati Medan Hospital must be further optimized through various training and special learning resources.